Fluoxetine induces photochemistry-derived oxidative stress on Ulva lactuca - Feijão, Eduardo; Cruz de Carvalho, Ricardo; Duarte, Irina A.; Matos, Ana Rita; Cabrita, Maria Teresa; Utkin, Andrei B.; Caçador, Isabel; Marques, João Carlos; Novais, Sara C.; Lemos, Marco F. L.; Reis-Santos, Patrick; Fonseca, Vanessa F.; et al. (Frontiers in Environmental Science, 2022)
Emerging pollutants impose a high degree of stress on marine ecosystems, compromising valuable resources, the planet and human health. Pharmaceutical residues often reach marine ecosystems, and their input is directly related to human activities. Fluoxetine is an antidepressant, and one of the most prescribed selective serotonin reuptake inhibitors globally and has been detected in aquatic ecosystems in concentrations up to 40 µg L-1. The present study aims to evaluate the impact of fluoxetine ecotoxicity on the photochemistry, energy metabolism and enzyme activity of Ulva lactuca exposed to environmentally relevant concentrations (0.3, 0.6, 20, 40, and 80 µg L−1). Exogenous fluoxetine exposure induced negative impacts on U. lactuca photochemistry, namely on photosystem II antennae grouping and energy fluxes. These impacts included increased oxidative stress and elevated enzymatic activity of ascorbate peroxidase and glutathione reductase. Lipid content increased and the altered levels of key fatty acids such as hexadecadienoic (C16:2) and linoleic (C18:2) acids revealed strong correlations with fluoxetine concentrations tested. Multivariate analyses reinforced the oxidative stress and chlorophyll a fluorescence-derived traits as efficient biomarkers for future toxicology studies.